The spatial distribution characteristics and influencing factors of key villages in rural tourism in China - Jiqiang Niu; Hao Guo; Weichun He; Feng Xu; Guangyu Zhang (PLoS ONE, 2025)
Rural tourism key villages in China serve as critical nodes driving the development of rural tourism. Based on a dataset of 1,195 key villages, this study employs Ripley’s K-function and geographic detector methods to investigate their spatial distribution patterns and influencing factors. The findings reveal: ① The spatial distribution of rural tourism key villages demonstrates a strong directional alignment toward major cities and tourist attractions; ② Significant regional disparities exist in aggregation scales, with the eastern region exhibiting a substantially higher concentration than the central and western regions; ③ Both natural environmental factors and socio-economic factors influence rural tourism key villages, with road network density, river network density, and per capita disposable income exerting the most pronounced effects. These results provide valuable theoretical insights and practical guidance for the differentiated development and rural revitalization of key villages in China’s rural tourism sector.